EFEKTIVITAS MODEL REALISTIC MATHEMATIC EDUCATION (RME) DENGAN MENGGUNAKAN ALAT PERAGA TERHADAP PRESTASI BELAJAR - A. Muhajir Nasir; Intan Eka Sari (Nurul Jadid University, 2019)
This research was experimental research that aimed to know and measure the effectiveness of applying the RME model by using props on cube and beam material students in class VIII SMP Negeri 5 Maros. The result of data analysis showed that the average of pre-test was 21,10 while the average of post-test was 76,67. Average of gain scores normalized 0.74 in the high category. Based on the t-test obtained 0.000 < 1/2α = 0.025 which means there was a significant increase. The post-test showed that 24 out of 30 learners (80%) had achieved the KKM score of Mathematics subjects.